Insectos y acaros que atacan el cultivo de la yuca en Colombia - Díaz, R.O.; Bellotti, Anthony C.; Schoonhoven, Aart van (1978)
Approx 20 insects and mites were found attacking cassava in several regions of Colombia at different growth stagcs and seasons. Thrips (Frankliniella williamsi), gall midges (Cecidomyiidae) and whiteflies (Bemisia sp. and Trialeurodes sp.) were present in greater than 50 percent of the plantations visited. Pests found at all stages of plant growth were the cassava fruitfly (Anastrepha sp.), leafhoppers (Empoasca sp.), lace bugs (Vatiga manihotae) and mites (oligonychus peruvianus). Pests limited to different regions were cutworms (Agrotis ipsilon and Spodoptera ,frugiperda) found in the states of Valle and Quindio and stemborers (Acanthoderes nigricans) in the state of Cauca. High parasitism of hornworm (Erinnyis ello) eggs was observed. Yield losses due to thrips were estimated. (AS)